2015
DOI: 10.4103/0976-9668.149087
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in retreatment patients of tuberculosis: A north Indian study

Abstract: Background:‘Retreatment’ for tuberculosis (TB) has long been a neglected area in global TB control India. However India disproportionately accounts for nearly half of retreatment TB cases notified globally. Sex differences vary in different age groups and in different parts of the world. The present study focuses on whether gender-based differences are present in notification rates, clinical presentation, and treatment outcomes of different subcategories of patients registered under category II of Revised Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(15 reference statements)
4
1
0
Order By: Relevance
“…The proportion of patients requiring a MDR-TB treatment regimen in the country in 2013 was not higher in comparison with previous years [ 16 , 17 ]. A predominance of males among retreatment TB cases was found in this study and this has also been reported elsewhere, although the reasons for this are not known [ 18 ]. “Atlantique-Littoral,” which houses Cotonou, the economic capital and the city with the highest density of population, always reports the highest number of TB cases in the country; and we are not surprised that this is also the case for retreatment TB cases.…”
Section: Discussionsupporting
confidence: 77%
“…The proportion of patients requiring a MDR-TB treatment regimen in the country in 2013 was not higher in comparison with previous years [ 16 , 17 ]. A predominance of males among retreatment TB cases was found in this study and this has also been reported elsewhere, although the reasons for this are not known [ 18 ]. “Atlantique-Littoral,” which houses Cotonou, the economic capital and the city with the highest density of population, always reports the highest number of TB cases in the country; and we are not surprised that this is also the case for retreatment TB cases.…”
Section: Discussionsupporting
confidence: 77%
“…Majority of the study participants 52.8% were in the age group 36 to 55 years. The study conducted by Sarpal et al 7 in Chandigarh, shows similar findings as our present study with respect to gender and age. As per the census 2011 data, Pondicherry has an average literacy rate of 85.85%, higher than the national average of 74%.…”
Section: Discussionsupporting
confidence: 92%
“…Among total 22 cases of re-treatment registered during the study period, 18 (81.8%) were males and 4 (18.1%) were females. In this study male-to-female ratio of re-treatment TB is 4.5: 1, which shows a male predominance similar to other studies like Srinath Sharath et al 5 in Andhra Pradesh, which shows 67% male patients and Sandeep Naveen et al 6 at Chandigarh shows 63.9% males with male: female ratio of 1.8: 1, while Ugra Srinath et al 7 shows 80% male predominance.…”
Section: Methodssupporting
confidence: 87%
“…Similar study by Srinath Sharath et al 5 in Andhra Pradesh shows 88% patients were in the age group of 15 -64 years. Sandeep Naveen et al 6 at Chandigarh conducted a study, which shows the mean ages of males and females were 38.79 ± 14.4 and 30.84 ± 15.85 years respectively, while Ugra Srinath et al 7 conducted a study which shows that the median age was 38 years.…”
Section: Agementioning
confidence: 99%